Security surveys : manufacturing plants, terminals and distribution centers, retail stores, office structures, private residences, closed and abandoned facilities - Floyd, William R. (Alexandria, Va. : ASIS International, 2008)
The book is made up of a set of guidelines for evaluating the security of: manufacturing plants, terminals and distribution centers, retail stores, office structures, private residences, closed and abandoned facilities
Includes appedices (p.49-362).
oif 03/06/14
Loan
Keywords: Dwellings -- Security measures; Industries -- Security measures; Crime prevention surveys; Security systems; Crime prevention surveys; Dwellings -- Security measures; Industries -- Security measures; Security systems